Analisis Gerak Tari Rangguk Desa Seberang Kecamatan Pesisir Bukit Kota Sungai Penuh - Niken Audia Ulfa; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2022)
This study aims to describe and analyze the motions of the Rangguk Dance in terms of the aspects of space, time, and energy. This type of research is qualitative research with a descriptive analysis method. Data collection techniques were carried out through literature studies, observations or observations, interviews, and documentation. The steps to analyze the data are data collection, data reduction, data presentation, and drawing conclusions. The study's results show that the motion of the Rangguk Dance in Seberang Village can be viewed from space, time, and energy. In the spatial aspect of the Rangguk dance, there are ten horizontal lines, six curved lines, and two diagonal lines, so the horizontal lines are dominant, which means that the Rangguk dance has a calm and balanced impression. The volume of the movement of the Rangguk Dance is 14 large volumes and four small volumes, so the dominant volume is the large volume which means it describes enthusiasm. The facing direction in the Rangguk Dance movement is 13 forward and three right diagonals, so the dominant facing direction is towards the front. Meanwhile, the focus of view is on the dominant activity of the Rangguk Dance going forward. The time aspect of the Rangguk Dance is more dominant in the medium tempo with a repetitive rhythm from beginning to end (repetitive) according to the drum accompaniment and the rhymes sung. In the energy aspect of the Rangguk Dance movement, in terms of intensity, there is a lot of integrity in each dance movement which is carried out repeatedly from start to finish, while the dominant pressure is many. Some movements have accents, then the quality that appears is also dominantly strong so that the Ragguk Dance seems enthusiastic and embodies the direction that makes the Rangguk Dance come alive.